Controlling modern government : variety, commonality, and change - Hood, Christopher, 1947- (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2004)
The book seeks to compare control of government across time, across policy domains and across countries. It examines what happened to control systems for public services over a generation or so, in three different domains of government and public policy within eight different state traditions. The three domains are prisons, higher education and the conduct of senior civil servants, and the eight different traditions comprise of Australia, the USA, Japan, France, Germany, the UK, the Netherlands and Norway.
Includes bibliographical references and index.
rpm 12/06/13
Loans
Keywords: Public administration; Comparative government